2012
DOI: 10.1556/amicr.59.2012.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Demodex mites in eyelashes among people of Oaxaca, Mexico

Abstract: This study was carried out to determine the prevalence of Demodex mites in eyelashes of people from different places from Oaxaca. One thousand and ten patients underwent epilation of eight eyelashes from each eye and they were processed to search Demodex which was found in 208 (20%) of the patients and among them male was more affected than female, 119 (57%) and 89 (43%), respectively. There was not found a relationship between clinical manifestations among these patients since 101 (49%) and 107 (51%) of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
0
24
1
3
Order By: Relevance
“…In our study, the prevalence of Demodex infestation in all patients (with and without blepharitis) was 48%, and most of the patients were at the age 70–79 years. It is relatively low, comparing to the results reported by other authors, e.g., Sedzikowska: 77% of infected patients in a group over 70 years [ 24 ], Czepita: 95% of patients aged 71–96 years [ 47 ], and Vargas-Arzola: 64% of patients aged 76–85 years [ 48 ]. In a study conducted by Post and coworkers, Demodex was observed in 84% of the general population aged 60 years and 100% of the general population aged above 70 years [ 38 ].…”
Section: Discussionmentioning
confidence: 69%
“…In our study, the prevalence of Demodex infestation in all patients (with and without blepharitis) was 48%, and most of the patients were at the age 70–79 years. It is relatively low, comparing to the results reported by other authors, e.g., Sedzikowska: 77% of infected patients in a group over 70 years [ 24 ], Czepita: 95% of patients aged 71–96 years [ 47 ], and Vargas-Arzola: 64% of patients aged 76–85 years [ 48 ]. In a study conducted by Post and coworkers, Demodex was observed in 84% of the general population aged 60 years and 100% of the general population aged above 70 years [ 38 ].…”
Section: Discussionmentioning
confidence: 69%
“…Demodex are cosmopolitan mites; so, their existence is recorded in many countries in all continents apart from Antarctica [ 15 , 16 ]. Currently, more than 100 different species of the Demodex genus are recognised.…”
Section: Introductionmentioning
confidence: 99%
“…Demodex er en type hårsekkmidd (follikkelmidd) som har stor utbredelse i befolkningen, tilsynelatende uavhengig av geografi, etnisitet og kjønn (Lacey, Kavanagh, & Tseng, 2009;Vargas-Arzola et al, 2012;Rather & Hassan, 2014;RusieckaZiółkowska, Nokiel, & Fleischer, 2014). Forekomsten ser ut til å vaere lav blant yngre individer, men øker kraftig med alderen og affiserer trolig majoriteten av alle individer over 50 år (Tabell 1).…”
Section: Introduksjonunclassified
“…Forekomsten ser ut til å vaere lav blant yngre individer, men øker kraftig med alderen og affiserer trolig majoriteten av alle individer over 50 år (Tabell 1). Note: Tabellen kombinerer resultater fra flere studier (Liu et al, 2010;Isa et al, 2011;Vargas-Arzola et al, 2012).…”
Section: Introduksjonunclassified